Obesity is associated with more sick leave and lower quality of life among Malay male security officers - Tan, Se Xian; Norhayati Ibrahim; Nuruljannah Johari; Roszanadia Rusli; Zahara Abdul Manaf (Penerbit Universiti Kebangsaan Malaysia, 2016)
Obesity is a risk factor for chronic diseases which can affect work productivity and physical function of employees particularly among those in security sector. The study aimed to determine the association between obesity with total days of sick leave and health related quality of life (HRQoL) among Malay male security officers. A cross-sectional study was conducted among Malay male security officers working in a Malaysian higher learning institution. Subjects were evaluated using anthropometric measurements, quality of life and number of sick leave taken within two months prior to the study. A total of 194 subjects (mean age 40.12 ± 11.41 years) were recruited. A total of 30.4% were obese, 39.7% were pre-obese and only 29.9% had normal body weight or underweight. Central obesity was observed in 57.7% of them and 87.1% shown excessive body fat percentage. Number of sick leave days was positively correlated with Body Mass Index (BMI) (r = 0.162, p = 0.024) and waist circumference (r = 0.181, p = 0.012). Score of the general health component was negatively correlated with BMI (r = -0.161, p = 0.025), waist circumference (r = -0.194, p = 0.007) and body fat percentage (r = -0.191, p = 0.008). Physical functioning score was lowest in obese subjects than normal and pre-obese subjects (p = 0.046). Score of the bodily pain component was positively correlated with waist circumference (r = 0.156, p = 0.030). Obesity is associated with number of sick leave days and quality of life in the studied group. Hence, body weight of the security staff should be monitored and appropriate intervention should be conducted to improve their work attendance and quality of life.